(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Three new genera, five new species are described, two genera are resurrected, two species are redescribed, nine new combinations are proposed. Some new data are given to the knowledge of the family Eriococcidae from Chile, Costa Rica, Ecuador, Paraguay, and Peru. These new data show that the family needs a wider study in the region.